Leveraging smart devices for automatic mood-transferring in real-time oil painting - Dutta T.; Gupta H.P. (My University, 2025)
Smart devices are becoming a convergent platform for multimedia sensing, computing, and communication. Digital oil painting (DOP) is a revolutionary technique where a digital artist uses a digital paintbrush to simulate the traditional bristle paintbrush of a painting to get an oil paint image. Artists explore the perceiving moods of people through colors and lights in the painting. In this paper, we attempt to exploit the convergence toward the problem of automatically transferring mood of a user in DOP in terms of ambient light and color perception. We propose a mood-based oil painting technique that can be implemented and used in current smart devices in real time without using any explicit hardware. The proposed technique is optimized significantly by reducing the processing time and power consumption. We also develop a prototype on Android operating system to create mood-based oil paint images. © 1982-2012 IEEE.